Living in Contaminated Radioactive Areas Is Not an Acute Risk Factor for Noncommunicable Disease Development: A Retrospective Observational Study. (9th September 2015) - Ishii, Takeaki; Tsubokura, Masaharu; Ochi, Sae; Kato, Shigeaki; Sugimoto, Amina; Nomura, Shuhei; Nishikawa, Yoshitaka; Kami, Masahiro; Shibuya, Kenji; Saito, Yasutoshi; Iwamoto, Yukihide; Tachiya, Hidekiyo
Abstract: Objective: Although much attention is now being paid to the health risks associated with nuclear disasters, reliable information is lacking. We retrospectively evaluated the health effects of living in highly contaminated radioactive areas in Japan. Methods: The health evaluation was conducted in Tamano district, Fukushima prefecture, in 2011 and 2012. The surface deposition density of cesium in Tamano was 600 to 1000 kBq/m 2 shortly after the Fukushima nuclear accident. Clinical parameters included body mass index, blood pressure, and laboratory examinations for blood cell counts, glucose levels, and lipid profiles. A screening program for internal and external exposure was also implemented. Results: One hundred fifty-five residents participated in the health evaluation. Significant decreases in average body mass index and blood pressure were observed from 2011 to 2012. Annual internal exposure levels did not exceeded 1 mSv in any participants. The levels of external exposure ranged from 1.3 to 4.3 mSv/y measured in the first test period but decreased to 0.8 to 3.6 mSv/y in the second test period. Conclusions: These findings suggest that inhabiting nuclear contaminated areas is not always associated with short-term health deterioration and that radiation exposure can be controlled within safety limitations. ( Disaster Med Public Health Preparedness . 2016;10:34–37)